Dinamika Eksplorasi Karier Mahasiswa: Peran Dukungan Sosial Orang Tua dan Status Sosial Ekonomi - Dini Rahma Lestari; Talitha Lintang Pertiwi (Universitas Hamzanwadi, 2026)
University students are in the emerging adulthood phase, characterized by increasing demands to prepare for careers and determine future directions. However, the high unemployment rate among university graduates in Indonesia indicates that students' career readiness remains suboptimal. One critical process in career preparation is career exploration, defined as the process of gathering information about oneself and the work environment to support career decision-making. This study aims to examine the influence of parental social support and family socioeconomic status on university students' career exploration. A quantitative approach with a cross-sectional design was employed, involving 205 active undergraduate students selected through purposive sampling. Multiple linear regression analysis was used to examine the relationships among the research variables. The results indicate that parental social support and family socioeconomic status simultaneously exert a significant influence on students' career exploration (R² = 0.185; F = 22.957; p < .001), jointly accounting for 18.5% of the variance in career exploration. These findings suggest that psychosocial support from parents plays a more dominant role than family economic conditions in shaping students' career exploration.